Two new species of Neocorynura from Guatemala (Hymenoptera: Halictidae: Augochlorini) with a key to the species known from the country - Smith-Pardo, Allan H. (Zootaxa, 2016)
This paper describes two new species of bees of the genus Neocorynura Schrottky from Guatemala. A taxonomic key to all five known species of the genus in Guatemala is provided and the male of N. centroamericana is described for the first time.